2019
DOI: 10.1111/ijpo.12531
|View full text |Cite
|
Sign up to set email alerts
|

Brown adipose tissue estimated with the magnetic resonance imaging fat fraction is associated with glucose metabolism in adolescents

Abstract: Summary Background Despite therapeutic potential against obesity and diabetes, the associations of brown adipose tissue (BAT) with glucose metabolism in young humans are relatively unexplored. Objectives To investigate possible associations between magnetic resonance imaging (MRI) estimates of BAT and glucose metabolism, whilst considering sex, age, and adiposity, in adolescents with normal and overweight/obese phenotypes. Methods In 143 subjects (10‐20 years), MRI estimates of BAT were assessed as cervical‐su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 50 publications
1
14
0
Order By: Relevance
“…Brown adipose tissue (BAT) has emerged as a promising target for obesity treatment and prevention due to its ability to increase energy expenditure through nonshivering thermogenesis [ 6 , 7 , 8 , 9 ]. BAT activation by cold exposure has been reported to improve glucose and lipid metabolism in rodents and humans due to its thermogenic function [ 10 , 11 , 12 ]. Therefore, strategies that enhance BAT activation and improve BAT function may confer beneficial diet-induced obesity and associated metabolic comorbidities.…”
Section: Introductionmentioning
confidence: 99%
“…Brown adipose tissue (BAT) has emerged as a promising target for obesity treatment and prevention due to its ability to increase energy expenditure through nonshivering thermogenesis [ 6 , 7 , 8 , 9 ]. BAT activation by cold exposure has been reported to improve glucose and lipid metabolism in rodents and humans due to its thermogenic function [ 10 , 11 , 12 ]. Therefore, strategies that enhance BAT activation and improve BAT function may confer beneficial diet-induced obesity and associated metabolic comorbidities.…”
Section: Introductionmentioning
confidence: 99%
“…The FF of BAT positively correlated with 2-hour glucose levels independent of sex, age, site, and adiposity, while T 2 * showed insignificance, suggesting the ability of BAT to control glucose levels and/or dissipate triglycerides and free fatty acids. 92 In a study by Franssens et al, 86 the absence of type 2 diabetes mellitus showed the most FF difference between supraclavicular and subcutaneous adipose tissue, demonstrating a lower BAT prevalence. FF was also used to explore the pharmacological mechanism of drugs used to treat type 2 diabetes mellitus.…”
Section: Type 2 Diabetes Mellitusmentioning
confidence: 94%
“…To detect and characterize BAT, chemical-shift encoding-based water–fat imaging techniques have been used on the supraclavicular adipose tissue in humans across all ages. Studies in infants ( 48 , 84 , 85 ), children ( 79 ), adolescents ( 86 ), and adults ( 81 , 87 94 ) have demonstrated the feasibility of this technique in humans. A favored method to measure BAT fat fraction is the measurement of the PDFF, which has been used in several studies for human BAT on grounds of its robustness and standardization ( 81 , 88 , 92 , 94 ).…”
Section: Characterizing Bat Water–fat Compositionmentioning
confidence: 99%
“…These correlations are of interest regarding potential therapeutic targets for obesity. More interestingly, it has been shown that activation of BAT increases glucose and triglyceride clearance in humans, potentially decreasing the risk of developing diabetes and other obesity comorbidities ( 4 , 86 , 108 , 112 , 113 ). In human adults with obesity, effects of cold and insulin on BAT activity were reported to be restricted ( 114 116 ).…”
Section: Characterizing Bat Water–fat Compositionmentioning
confidence: 99%